The Effect of Ophiopogonin C in Ameliorating Radiation-Induced Pulmonary Fibrosis in C57BL/6 Mice: An Update Study - Fu, Xiaobin; Li, Tingting; Yao, Qiwei (Frontiers in Oncology, 2022)
The aim of this study was to assess and update the protective effects and underlying mechanisms of Ophiopogonin C (OP-C), a biological active component separated and purified from Ophiopogon Japonicus, in ameliorating the radiation-induced pulmonary fibrosis in C57BL/6 mice accepted thoracic radiation. Methods and Materials 75 mice were randomly divided into five groups and accepted a dose of 12Gy whole thoracic radiation to establish the animal model of pulmonary fibrosis. Mice were treated with OP-C or dexamethasone (DEX) combined with/without cephalexin by gavage daily for 4weeks. All the mice were sacrificed at 28 weeks after the completion of the thoracic radiation. The serum levels of interleukin-6 (IL-6) and transforming growth factor-β1 (TGF-β1) were evaluated. Moreover, superoxide dismutase (SOD) in the lung tissue was also measured. The severity of fibrosis was evaluated by hydroxyproline (Hyp) contents of the lung tissue. The pathological changes in the five group were detected by hematoxylin and eosin staining (H＆E staining) and Masson trichrome staining. The expression of smooth muscle actin (SMA) was detected by immunohistochemical staining. Matrix-Metallo-Proteinases (MMP-2) and Tissue-Inhibitors of Metallo-Proteases (TIMP-2) by immunohistochemistry of the lung section staining were performed and semi-quantitative analysis was used to calculated the expression of MMP-2 and TIMP-2. Results Irradiated mice treated with OP-C or DXE combined with/without cephalexin significantly reduced mortality mice and levels of fibrosis according to 1) reducing the deposition of collagen and accumulation of inflammation cells and fibroblast, 2) downgrading levels of promote-fibrosis cytokines TGF-β1, 3) increasing activity of SOD in the lung tissue compared with irradiated mice without treatment. However, the levels of fibrosis were not any statistics differences among the irradiated mice treated with OP-C or DXE combined with/without cephalexin. Conclusion OP-C significantly ameliorates radiation-induced pulmonary-fibrosis and may be a promising therapeutic strategy for this disorder.